Prosthetic Rehabilitation of Completely Edentulous Mandibular Knife Edge Ridge: A Case Report - Patangwa, N; Shrestha, P; Verma, A; Sah, SK (Journal of Nepalese Prosthodontic Society, 2024)
Patients with conventional complete dentures may encounter various challenges, such as pain and soreness, particularly in the mandibular ridge during function. These issues may be related to a knifeedge ridge, severely atrophic ridge, and thin atrophic ridge mucosa. In such cases, a conventional complete denture with a rigid denture base further aggravates the condition. Hence, a resilient liner can be incorporated into the denture to avoid this. This clinical report presents the management of a patient with knife-edge mandibular ridge, flabby tissue, and undercuts. The patient had been previously rehabilitated with multiple dentures and had stopped wearing them due to pain. In this case, prosthetic rehabilitation was performed using a removable complete denture made with a heatcuring one-component silicone permanent soft relining material (Molloplast B, Detax, Germany). The incorporation of the resilient liner into the denture serves as a shock absorber by dissipating the kinetic energy generated from the impact of masticatory forces, thereby reducing trauma to the underlying mucosa.